NW : a novel - Smith, Zadie (Penguin Press, 2012)
"Four Londoners - Leah, Natalie, Felix, and Nathan - try to make adult lives outside of Caldwell, the council estate of their childhood. From private houses to public parks, at work and at play, their London is a complicated place, as beautiful as it is brutal, where the thoroughfares hide the back alleys and taking the high road can sometimes lead you to a dead end."--From publisher's information.